2023
DOI: 10.3390/horticulturae9010100
|View full text |Cite
|
Sign up to set email alerts
|

Study on Heat Resistance of Peony Using Photosynthetic Indexes and Rapid Fluorescence Kinetics

Abstract: To investigate the effects of high-temperature stress on the chlorophyll fluorescence induction kinetics of peony and to determine indicators for the rapid screening of varieties responding to high temperatures, three four-year-old peony variety, ‘Fengdanbai’, ‘Huhong’, and ‘Yinhongqiaodui’, were selected as materials. The photosynthetic curves (Pn-PAR) and fast chlorophyll fluorescence curves (OJIP curves) of peony leaves were measured at different times under high-temperature stress conditions (40 °C), the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…However, peony cultivars resistant to high temperature stress have a relatively low degree of time inhibition under high temperature stress and can maintain relatively high PSII actual light energy conversion efficiency [14]. Ji et al [15,16] investigated the changes in photosynthetic characteristics of P. ostii under high temperature stress and found that high temperature damaged the photosynthetic capacity and photosynthetic mechanism of peony leaves. At the same time, some studies have shown that exogenous additives can alleviate the photosynthetic characteristics of peonies under high temperature stress [17][18][19][20][21].…”
Section: Of 15mentioning
confidence: 99%
“…However, peony cultivars resistant to high temperature stress have a relatively low degree of time inhibition under high temperature stress and can maintain relatively high PSII actual light energy conversion efficiency [14]. Ji et al [15,16] investigated the changes in photosynthetic characteristics of P. ostii under high temperature stress and found that high temperature damaged the photosynthetic capacity and photosynthetic mechanism of peony leaves. At the same time, some studies have shown that exogenous additives can alleviate the photosynthetic characteristics of peonies under high temperature stress [17][18][19][20][21].…”
Section: Of 15mentioning
confidence: 99%
“…High temperature (HT) has adverse effects on photosynthesis, such as significantly reducing the maximum net photosynthetic rate ( P Nmax ), apparent quantum efficiency (AQE), and light-compensation point (LCP), and significantly increasing the light-saturation point (LSP) ( Djanaguiraman et al., 2020 ; Li et al., 2023 ). Previous studies demonstrated that gas exchange and photosynthesis had marked reduction under HT stress due to the inhibition of chloroplast and photosystem II (PSII) activity ( Salvucci and Crafts-Brandner, 2004 ; Allakhverdiev et al., 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a separate study, it was discovered that heat stress has a pronounced impact on the chlorophyll fluorescence properties of Rhododendron leaves [16]. Some studies including peony plants revealed that high-temperature stress directly influences chlorophyll fluorescence induction kinetics [17]. The direct impact of heat stress on plant fluorescence activity suggests its potential use as an indicator of heat stress [18].…”
Section: Introductionmentioning
confidence: 99%